Concordância espacial da assembléia de peixes de uma planície de inundação - PEREIRA, Camila Leite (2010)
The synchrony concept can be defined like the degree that different biologics systems show similar temporal evolution. Synchronies fluctuations in species are attributed to influence of ambient factors or individuals dispersion (distance of ambient). Thus, the objective this study was measured the ichthyofauna similarity among six environment of Parana River floodplain in responses to these different mechanisms. The biotic (ichthyofauna abundance) and abiotic (limnology gradients) dates was provided by NUPELIA. The statistical analyses supported in multivariate analyses applied in abundance matrices of fish species, limnology variables and connectivity distance among habitats. In such case the ichthyofauna dynamic varied asynchronous over time and space on the periods of 1987 to 19988 and 2006 to 2008. The period of greatest assemblage significant synchronies corresponded to intermediary period. The main reason of this synchrony was explain by the fluviometric quota, since the dynamic of this variable affected similarly the species abundance among locations. Altogether this study confirmed the theoretical support of Niche as a mechanism of assemblage synchrony in stable ecosystems. The neutral process wasn t a good model to explain the assemblage similarity between locations.